ANALYSING THE DETERMINANTS OF ARREARS RATE IN SHARIA MICROFINANCE: CASE STUDY OF BAITUT TAMWIL TAMZIS - Ar Rasyid, Muammar Farras; Faturohman, Taufik (Journal of Business and Management, 2018)
Abstract. This research has purpose to determine is there any statistically significant relationship between some factors of financing (plafon, tenor, main installment, purpose of financing, installment pattern, domain) and arrears rate. The methods used is multi-linear regression and logistic regression. This research uses two methods because the dependent variable could interpreted into two ways, which are continuous and binary. The data used is secondary data from Baitut Tamwil Tamzis database. The data used is financing data that has maximum plafon on Rp10,000,000.00. It consist of independent variable: plafon, tenor, and main installment, domain, purpose of financing, installment pattern. For the dependent variable used is the arrears. The ar rears is categorized into four risk index categories. After performed the multi-linear regression, the variables that have statistically significant relationship are productive financing, Cijerah, and monthly pattern, and after performed the logistic regression, there is one more variable that has statistically significant relationship, which is main installment.Keywords: Arrears, Baitut Tamwil, Determinants, multi-linear regression, logistic regressionz